Disease advocacy organizations catalyze translational research - Terry, Sharon F. (Frontiers Media S.A., 2013)
Disease advocacy organizations have long played an important role in the continuum from basic science to therapy development in rare disease research. PXE International has led the field in innovative ways, venturing into specific activities that have traditionally been conducted by scientists. As lay founders, we have engaged in gene discovery, gene patenting, diagnostic test development, epidemiological studies, clinical trials, and therapy research and development. This article will describe the steps that we took, and the ways in which we have scaled these efforts for the larger community.